EKSPEKTASI DAN PERSEPSI MAHASISWA TERHADAP KUALITAS PENDIDIKAN PADA UNIVERSITAS SOERJO NGAWI - Rozalina Novianty; Lina Sugiyanto; Istiana Wijayanti Mala (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2016)
This research is conducted to know students expectation and perception to the quality of education at University of Soerjo Ngawi, in study program of management. The research was using SERVQUAL (Service Quality) method which founded by Parasuraman, et.al. Based on the data analysis, the student’s expectation to quality was not enough than the actual quality. We could see from the result between quality-expectation and quality-perception that showed the big differences result.